Potensi Penghambatan Enzim Tirosinase dengan Ekstrak Etanol Terstandar dan Fraksi Etil Asetat Kulit Bengkoang (Pachyrhizus erosus L. - Zainur Rahman Hakim; Ratna Djamil; Novi Yantih; Ocitania Sanasih; Benny Iskandar (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
This study examined the tyrosinase inhibitory potential of bengkoang peel standardised ethanolic extract and ethyl acetate fractions. 450 g of bengkoang peel powder (Pachyrhizus erosus L.) was macerated with 96% ethanol for 2 x 24 h, filtered, and concentrated till viscous. Extract standardisation uses specific and non-specific parameters. Microplate colorimetric tyrosinase inhibition assays were performed. The result of plant determination identified the bengkoang peel as Pachyrhizus erosus (L.) Urb. The organoleptic test revealed a brownish-yellow viscous extract, fresh smell, and bitter taste. Ethanol-soluble extract was 47.60% and water-soluble 22.42%. Bengkoang peel ethanolic extract includes alkaloids, flavonoids, saponins, tannins, and steroids. The non-specific parameters showed loss of drying (9.71%), water content (7.28%), total ash (9.91%), acid-insoluble ash (3.68%), no residual solvent content, lead content (-0.2324±0.1729), cadmium content (-0.0841±0.3418), TPC of 1 x 101 CFU/g, and TYMC of 2.26 x 102 CFU/g. The ethanol extract (103.9263) and ethyl acetate fraction (81.8606) IC50 values of bengkoang peel decrease tyrosinase enzyme activity compared to control (25.1235 ppm). These results show that the ethanol extract met both particular and non-specific quality standards. Bengkoang peel ethyl acetate inhibited tyrosinase.